On The Rim : Looking For The Grand Canyon - Neumann, Mark (Book collections on Project MUSE., 1999)
Why do nearly five million people travel to the Grand Canyon each year? Mark Neumann answers this question with a book as compelling as the panoramic vistas of the canyon. In On the Rim, he describes how the Grand Canyon became an internationally renowned tourist attraction and cultural icon, and delves into the meanings the place holds for the individuals who live, work, and travel there. "In the chasm's dizzying depths and flamboyant displacement of solid ground, as well as in the perceptions of those drawn there-explorers and day-trippers, employees and outlaws, artists and fast-buck artist